IMPLEMENTASI MEDIA PEMBELAJARAN POP UP BOOK DIGITAL DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VII-B DI SMP NEGERI 14 JAKARTA - Rangga Trilaksana; Desy Safitri; Sujarwo Sujarwo (STKIP Subang, 2026)
The low learning outcomes in Social Studies (IPS) at SMP Negeri 14 Jakarta, particularly in class VII B which recorded the lowest average score among all seventh-grade classes, indicate the need for more effective instructional media innovation. This study aims to examine the implementation of digital pop-up book learning media in improving the Social Studies learning outcomes of class VII-B students at SMP Negeri 14 Jakarta. The method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of two cycles covering the stages of planning, action, observation, and reflection. The research subjects comprised 34 students from class VII-B, selected based on having the lowest average score among all seventh-grade classes. The results show that the implementation of digital pop-up book learning media significantly improved both student learning outcomes and engagement, as evidenced by an increase in the achievement of Learning Outcome Indicators (IPH) from 70% in cycle 1 to 85% in cycle 2, as well as an increase in the average student engagement rate from 49% in cycle 1 to 82% in cycle 2. These findings demonstrate that digital pop-up book media is effective in improving Social Studies learning outcomes while also encouraging students' active participation in the learning process.